“Anabase” di Saint-John Perse: Alcune note sulla traduzione russa di Georgij Adamovič e e Georgij Ivanov (TEST Ticontre. Theory Text Translation, 2023)
The present work is dedicated to the Russian translation of the prose poem Anabase by Saint-John Perse (1924), produced by Georgij Adamovič and Georgij Ivanov in 1926. On the basis of archival materials conserved at the Fondation Saint-John Perse, in the first part, the article reconstructs the context in which the emigré-publisher Povolockij decided to entrust the two poets with the Russian version of the poem, as well as the meager bibliography dedicated to it. At the center of the second part is an examination of the translation, in particular of the limited lexical corpus identified in the classic study by Monique Parent (1960) on Anabase («pensée», «songe», «esprit»). The translation choices are also studied through the use of the national corpus of the Russian language, and specifically the parallel French-Russian corpus and the poetic corpus. Il presente lavoro è dedicato alla traduzione russa del poema in prosa Anabase di Saint-John Perse (1924), realizzata da Georgij Adamovič e Georgij Ivanov nel 1926. Sulla base di materiali di archivio conservati alla Fondation Saint-John Perse di Aix-en-Provence l’articolo ricostruisce nella prima parte il contesto in cui l’editore Povolockij, emigrato a Parigi, decise di affidare ai due poeti la versione russa del poema, nonché la scarna bibliografia ad essa dedicata. Al centro della seconda parte è l’esame della traduzione, in particolare del limitato corpus lessicale individuato nel classico studio di Monique Parent (1960) su Anabase («pensée», «songe», «esprit»). Le scelte traduttive sono studiate anche mediante l’utilizzo del corpus nazionale della lingua russa, e specificamente del corpus parallelo francese-russo e del corpus poetico.